ANALISIS IMPLEMENTASI NILAI-NILAI PANCASILA DALAM PEMBENTUKAN KARAKTER DISIPLIN SISWA KELAS IV DI SDN PAKANDANGAN BARAT II - Alfiatus Sholehah; Sultan Samak; Agus Wahdian (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the implementation of Pancasila values in the formation of disciplined character of fourth grade students at SDN Pakandangan Barat II and to identify the challenges and strategies implemented by the school. A descriptive qualitative approach was used in this study, with data collection methods through interviews, observations, and documentation. The results of the study indicate that Pancasila values are implemented through daily habits, teacher role models, and extracurricular programs. However, the main obstacles faced are students' lack of understanding of Pancasila values, minimal parental involvement, and the influence of the less conducive outside school environment. To overcome these challenges, the school implemented a reward and punishment strategy, strengthened the role of teachers as role models, and increased parental involvement in the formation of students' disciplined character. This study recommends closer synergy between schools, families, and the social environment in instilling Pancasila values in order to form a strong and sustainable disciplined character in elementary school students. This study aims to analyze the implementation of Pancasila values in the formation of disciplined character of fourth grade students at SDN Pakandangan Barat II and to identify the challenges and strategies implemented by the school. A descriptive qualitative approach was used in this study, with data collection methods through interviews, observations, and documentation. The results of the study indicate that Pancasila values are implemented through daily habits, teacher role models, and extracurricular programs. However, the main obstacles faced are students' lack of understanding of Pancasila values, minimal parental involvement, and the influence of the less conducive outside school environment. To overcome these challenges, the school implemented a reward and punishment strategy, strengthened the role of teachers as role models, and increased parental involvement in the formation of students' disciplined character. This study recommends closer synergy between schools, families, and the social environment in instilling Pancasila values in order to form a strong and sustainable disciplined character in elementary school students.